Comparative Study between Clinical and Sonographic Estimation of Fetal Weight in Third Trimester of Pregnancy and Its Relationship with Actual Birth Weight (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):157-63.The abstract of this article is available on the PubMed website